Testing Lab-on-a-Chip Technology for Culturing Human Melanoma Cells under Simulated Microgravity - Przystupski, Dawid (Cancers (Basel), 2021)
SIMPLE SUMMARY: The main aim of this study was to investigate whether all-glass Lab-on-a-Chip (LOC) platforms can be applied to cancer cell research performed under simulated microgravity. For this purpose, we designed and constructed a 3D-clinostat—a device that allows us to investigate the effect of simulated microgravity (sµg) in biological studies. We used human keratinocytes HaCaT and skin melanoma A375 cells cultured on LOCs as a research model. Preliminary analyses included optimization of LOCs structure and evaluation of their biocompatibility. For both cell lines, we demonstrated that LOCs can be successfully implemented in microgravity research. These results are a good base to conduct further research on the possible application of LOCs systems in cancer research in space, especially for microgravity studies. ABSTRACT: The dynamic development of the space industry makes space flights more accessible and opens up new opportunities for biological research to better understand cell physiology under real microgravity. Whereas specialized studies in space remain out of our reach, preliminary experiments can be performed on Earth under simulated microgravity (sµg). Based on this concept, we used a 3D-clinostat (3D-C) to analyze the effect of short exposure to sµg on human keratinocytes HaCaT and melanoma cells A375 cultured on all-glass Lab-on-a-Chip (LOC). Our preliminary studies included viability evaluation, mitochondrial and caspase activity, and proliferation assay, enabling us to determine the effect of sµg on human cells. By comparing the results concerning cells cultured on LOCs and standard culture dishes, we were able to confirm the biocompatibility of all-glass LOCs and their potential application in microgravity research on selected human cell lines. Our studies revealed that HaCaT and A375 cells are susceptible to simulated microgravity; however, we observed an increased caspase activity and a decrease of proliferation in cancer cells cultured on LOCs in comparison to standard cell cultures. These results are an excellent basis to conduct further research on the possible application of LOCs systems in cancer research in space.